Clinical course and neurological outcomes of cerebral venous sinus thrombosis: A single center retrospective observational study. - Pasook Sitthilok; Piangrawee Niprapan; Adisak Tantiworawit; Teerachat Punnachet; Nonthakorn Hantrakun; Pokpong Piriyakhuntorn; Thanawat Rattanathammethee; Sasinee Hantrakool; Ekarat Rattarittamrong; Lalita Norasetthada; Chatree Chai-Adisaksopha (PLoS ONE)
Background Cerebral venous sinus thrombosis (CVST) is a rare type of thrombosis that affects the cerebral venous system. The data on neurological outcomes are limited. Objectives This study aimed to investigate the neurological outcomes of CVST, contributing factors, clinical presentation, treatment and mortality. Methods This was a single-center, retrospective study at a university-based referral hospital in Thailand. Consecutive patients diagnosed with CVST between January 2010 and December 2020 were included. Outcomes were neurological outcomes measured by modified Rankin Scale (mRS), anticoagulant treatment, recurrence, and mortality. Results One hundred and seven CVST patients were included with a mean age (± SD) of 42.7 ± 20.4 years. Following the treatment, neurological outcomes significantly improved, with the proportion of patients with mRS 0-1 increasing from 18.7% at diagnosis to 83.2% and 85.1% at three and six months, respectively (P < 0.001). Clinical variables were associated with residual neurological symptoms (mRS≥1) included age ≥ 50 years (OR 4.1, 95% CI; 1.7-9.4, P 0.001), male sex (OR 3.0, 95%CI; 1.4-6.6, P 0.006), the thrombus involvement in deep sinus system (OR 6.1, 95%CI; 1.1-76.9, P 0.04) and cerebral vein and dural sinus thrombosis (CVT) risk score ≥ 1 (OR 3.1, 95%CI; 1.3-7.5, P 0.014). Patients whose CVST was associated with hormonal therapy were found to have a lower risk of residual neurological symptoms (OR 0.2, 95%CI 0.1-0.6, P 0.004). Hormonal therapy was associated with anticoagulant discontinuation (OR 2.7, 95% CI 1.1-7.0; P = 0.04). The presence of malignancy increased the risk of bleeding (OR 5.8, 95% CI 1.4-24.1; P 0.016). Overall mortality was 2.8%. Of which 50% were related to major bleeding. Conclusions A significant improvement in neurological outcomes was observed at 3 and 6 months after diagnosis. Older age, male sex, thrombus involvement in deep sinus system were associated with residual neurological symptoms.